Leukemic Infiltration of the Kidney - Widagdo Widagdo; Iskandar Wahidiyat; A. H. Markum (Indonesian Pediatric Society, 1974)
The case presented below is probably the first report concerning renal involvement of leukemia ever published in the Indonesian literature.